2018
DOI: 10.1016/j.childyouth.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Japanese residential care quality and perceived competency in institutionalized adolescents: A preliminary assessment of the dimensionality of care provision

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
(41 reference statements)
1
5
1
Order By: Relevance
“…First, EA-HOME-JP has not yet been validated. Lower variability in the physical environment is congruent with the results of Zhang et al (2018) and may be attributed to the application of the national standards for residential care institutions, which are set by the Ministry and that firmly regulate structural design and physical environment. On the other hand, when using EA-HOME-JP as a tool to compare residential care institutions with foster homes and family household environments, the subscale of physical environment may become meaningful.…”
Section: Limitationssupporting
confidence: 64%
See 4 more Smart Citations
“…First, EA-HOME-JP has not yet been validated. Lower variability in the physical environment is congruent with the results of Zhang et al (2018) and may be attributed to the application of the national standards for residential care institutions, which are set by the Ministry and that firmly regulate structural design and physical environment. On the other hand, when using EA-HOME-JP as a tool to compare residential care institutions with foster homes and family household environments, the subscale of physical environment may become meaningful.…”
Section: Limitationssupporting
confidence: 64%
“…In addition, low internal consistencies for the subscales, as indicated by the low Cronbach alpha levels in the current study, call into question the validity of the observed associations and demand careful interpretation of the results. The Cronbach alphas in the current study were lower than those indicated by Zhang et al (2018). Thus, EA-HOME-JP question items must be scrutinized by further statistical analyses, such as factor analysis, using a larger sample.…”
Section: Limitationscontrasting
confidence: 59%
See 3 more Smart Citations